Historical development of subseries of the harmonic series - Sarmiento-Sarmiento , Edilberto; Pulido-Segura , Carmen Leonor; Riaño-Pulido , Andrés Jhovany (Visión electrónica, 2019)
A historical development of the harmonic series subseries that are convergent is made. It is well known that this series diverges, the series of Kempner (1914) and Irwin (1916) which are obtained by removing from the harmonic series a certain amount of numbers containing the digit 9, since that, several authors have analyzed the variations of this idea, determining the convergence of similar sub-sums of the harmonic series and calculating or estimating the sums when they are convergent, until Lubeck and Ponomarenko (2018) obtain a result that characterizes the converging subsums of the harmonic series.